A desirable convulsive threshold : Some reflections about electroconvulsive therapy (ect) - Loria, Emiliano (Array, 2020)
Long-standing psychiatric practice confirms the pervasive use of pharmacological therapies for treating severe mental disorders. In many circumstances, drugs constitute the best allies of psychotherapeutic interventions. A robust scientific literature is oriented on finding the best strategies to improve therapeutic efficacy through different modes and timing of combined interventions. Nevertheless, we are far from triumphal therapeutic success. Despite the advances made by neuropsychiatry, this medical discipline remains lacking in terms of diagnostic and prognostic capabilities when compared to other branches of medicine. An ethical principle remains as the guidance of therapeutic interventions: improving the quality of life for patients. Unfortunately, psychotropic drugs and psychotherapies do not always result in an efficient remission of symptoms. In this paper I corroborate the idea that therapists should provide drug-resistant patients with every effective and available treatment, even if some of such interventions could be invasive, like Electroconvulsive Therapy (ECT). ECT carries upon its shoulders a long and dramatic history that should be better investigated to provide new insights. In fact, ECT has attracted renewed interest in recent years. This is due to the fact that antidepressant drugs in younger patients show often scarce effectiveness and unpleasant side-effects. Moreover, I show that, thanks to modern advances, ECT may work as a successful form of treatment for specific and rare cases, such as severe depression (with suicide attempts) and catatonia.